2016
DOI: 10.1155/2016/1719720
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TLR4 on B Cell Activation and Anti-β2GPI Antibody Production in the Antiphospholipid Syndrome

Abstract: High titer of anti-β 2-glycoprotein I antibodies (anti-β 2GPI Ab) plays a pathogenic role in antiphospholipid syndrome (APS). Numerous studies have focused on the pathological mechanism in APS; however, little attention is paid to the immune mechanism of production of anti-β 2GPI antibodies in APS. Our previous study demonstrated that Toll-like receptor 4 (TLR4) plays a vital role in the maturation of bone marrow-derived dendritic cells (BMDCs) from the mice immunized with human β 2-glycoprotein I (β 2GPI). TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 98 publications
0
12
0
1
Order By: Relevance
“…RNA‐seq technology also led to the discovery that liver B cells from neonatal RRV‐BA mice have activation of multiple innate immune pathways, including up‐regulation of TLR4 and TLR7/9. It was recently shown that TLR4 activation plays a key role in promoting the maturation of immature and transitional B cells . Recognition of nucleic acids (NAs) by TLRs 7 and 9 on B cells results in aberrant B‐cell activation, with subsequent production of proinflammatory cytokines .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA‐seq technology also led to the discovery that liver B cells from neonatal RRV‐BA mice have activation of multiple innate immune pathways, including up‐regulation of TLR4 and TLR7/9. It was recently shown that TLR4 activation plays a key role in promoting the maturation of immature and transitional B cells . Recognition of nucleic acids (NAs) by TLRs 7 and 9 on B cells results in aberrant B‐cell activation, with subsequent production of proinflammatory cytokines .…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that TLR4 activation plays a key role in promoting the maturation of immature and transitional B cells. (44) Recognition of nucleic acids (NAs) by TLRs 7 and 9 on B cells results in aberrant B-cell activation, with subsequent production of proinflammatory cytokines. (21,45) Potential NAs stimulating B cells in murine BA may include microbially derived NAs (i.e., RRV) or endogenous NAs from damaged bile duct epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of TLR4 in intestinal epithelial cells not only induces the activation of NF‐kB, but also leads to increased cell apoptosis, which results in the loss of intestinal integrity . In addition, TLR4 is also expressed on immune cells including dendritic cells, macrophages, B cells, and T cells . The over‐activation of TLR4 in these cells is strongly associated with immune dysfunction and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The “second hit” relates to an additional factor that further exacerbates a pro-thrombotic state (for example inflammation), which in combination with aPL antibodies ultimately induces thrombosis ( 19 ). The theory of a “second hit” is further supported by recent studies, which have implicated Toll Like Receptors (TLR) in mediating the inflammatory response in the pathogenesis of APS ( 20 , 21 ). However, in the context of pediatric APS, there is a notable absence of other classical pro-thrombotic risk factors including both pathological states (such as hypertension) and lifestyle related factors such as smoking.…”
Section: Pathogenesis Of Apsmentioning
confidence: 96%